Ineficacia jurídica del art. 18 numeral 22 de la ley notarial del Ecuador en relación al divorcio por mutuo consentimiento - González Cáceres, Alex Patricio (2015)
There is not rare the existence of frequent cases in which it victimizes and victimizer are spouses between if, coming to him the violence inside the family one from the principal social problems of the actuality. But the marriage does not take the violence as the only source of conflicts, there exist also frequent cases of adultery, damages, hostile attitude, across which the responsible spouse produces an affectation to the physical, psychological and moral integrity in against to the honor of the attacked spouse; without that in this case to guaranteed to the offended person the indemnity of the damages caused in his against. Inside the Statute law, little or almost nothing it has treated about the juridical, social, psychological and economics conflicts of the juridical institution of the marriage; in spite of that in the last times it has suffered a whole splitting, principally for the absence of harmony inside the home, front to which the right could not have given solutions of objective applicability. Except arranged in the Civil Code, regarding the grounds of divorce; but, when inside the couple have existed facts hurt the intrinsic rights of the human being, as the right to the honor, to the good reputation, to not violence, how must it operate the Family law?; is it possible to allow that this type of acts stay without legal response?. With questioning these, there is demonstrated that our Civil Code, needs to be reformed, incorporating the being necessary that the judge has the legal faculty to arrange the indemnification for the hurts and prejudices caused to verify any of three grounds before mentioned indepenced.